Pengembangan E-Modul Berbasis Inkuiri Terbimbing untuk Meningkatkan Kemandirian Belajar dan Hasil Belajar Peserta Didik pada Materi Koloid - Yunus, Ayu; Danial, Muhammad; Muharram, Muharram (Chemistry Education Review (CER), 2022)
This study is a development research that aims (1) to develop a guided inquiry-based learning module in increasing learning independence and learning outcomes (2) to produce a guided inquiry-based e-Module which is valid, practical, and effective in increasing learning independence and learning outcomes. The development model used in this study is the ADDIE development model. The guided inquiry-based e-Module developed had gone through the validation stage by experts so that based on the validation results it is declared valid and based on the results of trials in class it is declared practical and effective. e-Modules and other research instruments are stated to have met the criteria for validity in valid category. Based on the research data, the e-Module have met the practicality criteria because the practicality test is related to: (a) the implementation of the guided inquiry-based learning e-Module with the average value of M=1.79 in the interval (1.5≤M≤2 ,0) with implemented entirely category; (b) positive teacher’s response with a percentage of 89% in very practical criteria; and (c) very positive students’ responses with a percentage of 81% in very practical criteria. The guided inquiry-based e-Module is stated to be effective because it has met the effectiveness criteria with the results: (a) increasing students' learning independence from before treatment 57.02% to 79.63% after the treatment; (b) the learning outcomes meet the effective criteria for the n-gain value with an increase in learning outcomes by 0.78 in high category. e-Module was developed with the help of 3D Pageflip Professional software. The guided inquiry-based e-Module that was developed includes elements consisting of: (1) cover, containing the identity of the colloid e-Module, (2) instructions for using the e-Module, (3) KD and learning indicators, (4) a brief Colloid material at certain meetings, (4) learning videos, and (5) learning activities.